ANALISIS STRATEGI DAN TANTANGAN TUTOR DALAM MENGAJARKAN KETERAMPILAN BERBICARA BAHASA INGGRIS: STUDI TENTANG KURSUS BAHASA INGGRIS BEC - Yoni Yoni; Yelni Erniyati (BASIS (Bahasa dan Sastra Inggris), 2026)
This study aims to analyze the strategies and challenges faced by tutors in teaching English speaking skills at the British English Course (BEC) Camp in Sungai Penuh, Kerinci. A descriptive qualitative method was employed, with data collected through observations, semi-structured interviews, and documentation. The participants were two experienced tutors who have been teaching for a minimum of three years. Data were analyzed using thematic analysis to identify key patterns and themes. The findings revealed that tutors employed strategies such as mouth movement training for pronunciation and the implementation of an immersive "English Area" environment. Tutors also adapted their teaching methods based on students’ abilities and personalities. The challenges encountered included internal factors like anxiety and lack of confidence, and external factors such as local language interference and limited fluency. The study emphasizes the importance of a personalized and flexible approach to teaching speaking skills to support students' language development effectively.